A novel and efficient method to induce allospecific CD8+ memory T lymphocytes. Issue 10 (31st August 2021) - Yang, Lei; Huang, Qingyun; Fu, Jianping; Lin, Zhimin; Mao, Qiqi; Zhao, Lili; Gao, Xingxin; Chen, Songlin; Hua, Guangzong; Li, Sheng
Abstract: The aim of the current study was to establish a simple method for effectively inducing memory T lymphocytes by the intraperitoneal injection of spleen lymphocytes into mice. In total, 75 mice were divided into the following groups: an injection group administered three doses of spleen lymphocytes (1 × 10 6, 5 × 10 6, and 1 × 10 7 cells), a transplantation group in which a 0.25‐cm 2 skin section from C57BL/6 mice was transplanted onto the back of the recipient, and a control group in which an equal volume of phosphate‐buffered saline was injected. At 1, 2, or 3 months following transplantation, the following parameters were evaluated: quantity of T lymphocytes, percentage of cluster of differentiation 8 + (CD8 + ) memory T cells, and proliferation index of purified CD8 + memory T cells. No significant differences among groups were detected at 1 month ( p > .05). However, the injection group administered 1 × 10 6 cells exhibited the highest proportion of CD8 + memory T cells among all groups at 2 months, and the proportions of CD8 + T cells were higher in the three injection groups than in the skin transplantation and control groups at 3 months. The proportions of memory T cells were higher in the injection groups administered 5 × 10 6 or 1 × 10 7 cells than in the skin transplantation and control groups at 3 months. The newly established method effectively induces memory T lymphocytes via the intraperitoneal injection of spleen lymphocytes in vivo and has potential applications in the field of immunotherapy. Abstract : Processing of donor samples: The details of the memory T‐cell induction strategy are shown in Figure 1. All mice underwent aseptic surgery. The donor C57BL/6 mice were sacrificed by neck dislocation, and the skin grafts were cut into sections of 0.25 cm 2 followed by disinfection by soaking in 75% alcohol for 5 min. The spleens of donor mice were aseptically excised and used to make lymphocyte suspensions. The lymphocytes were counted using a hemocytometer, diluted to 1 × 10 6, 5 × 10 6, and 1 × 10 7, resuspended in 0.2 ml of phosphate‐buffered saline (PBS), and used for intraperitoneal injections. Skin transplantation and injections: The mice in the skin transplantation group were anesthetized using 0.1 ml/10 g 1% sodium pentobarbital following systemic disinfection. A 0.25‐cm 2 section of skin on the back of each mouse was replaced with the donor skin and sutured around the edge of the section. Mice in the injection groups were injected with three doses (1 × 10 6, 5 × 10 6, or 1 × 10 7 cells) of the prepared lymphocyte suspensions, taking care to avoid puncturing the internal organs, and the same volume of PBS was injected into control mice. Following surgery, mice in the skin transplantation group were disinfected with 75% alcohol daily to avoid infection. The donor skin that was sutured onto the back of the recipients became necrotic and was shed 8 days postoperation, with gradual wound healing. Collection of T lymphocytes: After the mice were sacrificed by cervical dislocation, they were placed in the right lateral position, the skin surface was disinfected with 75% alcohol, the skin was cut with sterile surgical instruments, and the spleen was removed. The spleen was placed in a vessel containing PBS, and cells in the spleen were carefully collected with syringes and fully suspended in PBS. An autoclaved filter was used to filter the cell suspension. Centrifugation was performed and the supernatant was discarded. Red cells in the pellet were lysed by the addition of red blood cells lysate buffer. Cells were washed with PBS three times and centrifuged to obtain PBMCs, which were ready for subsequent experiments.